2020
DOI: 10.1111/jfbc.13149
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation processes in soymilk isoflavones to enhance anti‐inflammatory potential in intestinal cellular model

Abstract: The present study investigated, in in vitro cellular model, the modulation of intestinal inflammation by biotransformed soymilk with tannase and probiotic strains. The ability to reduce the generation of intracellular reactive oxygen species (ROS) and the antioxidant power of soy extracts were also evaluated. The results showed changes in isoflavones profile after biotransformation processes, with a significative enhancement in aglycones content. Reduction in intracellular ROS production and improvement in ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…A previous study that used the combination of Bifidobacterium lactis and Lactobacillus casei resulted in an increase in the daidzein content (from 1 to 7/100 g of sample dry weight) and genistein (from 2 to 5/100 g of the dry weight sample) [ 8 ]. In another study, a combination of the same strains of B. lactis (BLC1) and L. casei (MB151) resulted in an increase in daidzein, genistein, and glycitein around 10%, 225%, and 36%, respectively, compared to the control [ 12 ]. A previous study of our research group was carried out using different bacterial strains to ferment a soymilk extract, including Streptococcus thermophilus (YF-L811), Lactobacillus delbrueckii ssp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study that used the combination of Bifidobacterium lactis and Lactobacillus casei resulted in an increase in the daidzein content (from 1 to 7/100 g of sample dry weight) and genistein (from 2 to 5/100 g of the dry weight sample) [ 8 ]. In another study, a combination of the same strains of B. lactis (BLC1) and L. casei (MB151) resulted in an increase in daidzein, genistein, and glycitein around 10%, 225%, and 36%, respectively, compared to the control [ 12 ]. A previous study of our research group was carried out using different bacterial strains to ferment a soymilk extract, including Streptococcus thermophilus (YF-L811), Lactobacillus delbrueckii ssp.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, in some studies mentioned above, the combination of fermentative and enzymatic bioprocesses using the enzyme tannase or β-glucosidase resulted in a superior synergistic effect compared to bioprocesses alone [ 12 , 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of PSE was selected based on previous publication on the in vitro studies of polyphenolic extracts (de Ávila et al, 2019;Hiramatsu et al, 2020), which showed that the concentration range of 2.5-1000 µg/ml in cell viability for MTT assay is appropriate to proceed with further cell studies.…”
Section: Cell Viability: Mtt Assaymentioning
confidence: 99%
“…[19][20][21] In addition, some isoflavones in licorice also exhibit certain antiinflammatory, antioxidant and antitumor activities, such as licorice glabritin and licorice isoflavones A. [22] Glycyrrhizic acid is a flavonoid derived from coumarin and has also been shown to have antioxidant, antiviral, and liver protective effects. [23] However, in the research of antioxidants of LCF, most researchers only explore its antioxidant capacity through experiments, and few people study its antioxidant mechanism.…”
Section: Introductionmentioning
confidence: 99%